Analisis Pengaruh Pengalaman Pemasaran Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan (Studi pada Coffee Toffee Malang) - Adi, Faris Rakha (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research aims to determine the influence of Experiential Marketing - through its dimensions, ofsense, feel, think, act, and relate – and Customer Satisfaction on Customer Loyalty in Coffee Toffee Malang. This explanatory research which explains the causal relation between its existing variables through hypothesis testing. The result of this research is that four dimensions of Experiential Marketing, which are sense, feel, think, and act, have a positive and significant effect on Customer Satisfaction where the dimension of sense is the dominant dimension, and relate has the smallest significance. Futhermore, four dimensions of Experiential Marketing, which are sense, think, act, and relate have a positive and significant effect on Customer Loyalty, where the dimension of relate is the dominant dimension, and sense has the smallest significance. The tvalue of the influence of Customer Satisfaction on Customer Loyalty reaches 1.972, which means that Customer Satisfaction significantly and positively influences Customer Loyalty.Keywords: Experiential Marketing, Customer’s Satisfaction, Customer’s Loyalty, Coffee Toffee Malang